2021
DOI: 10.1002/cjce.24314
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution behaviour of different rank coals in L‐glutamic acid N, N‐diacetic acid chelating agent: Implications to enhance coalbed methane recovery by acid stimulation

Abstract: Acid stimulation is a promising method in improving coal seam permeability by demineralization in coal cleats. However, using conventional acids such as HCl and mud acid (12 wt.% HCl + 3 wt.% HF) may cause clay breakage, migration, and precipitation, leading to formation damage. In this study, we investigated the effect of L‐glutamic acid N, N‐diacetic acid (GLDA) chelating agent treatment on the dissolution behaviour of lignite (Coal L) and anthracite (Coal A), collected from Er′Lian Basin and Qinshui Basin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Chemical stimulation is divided into types of acid and oxidation stimulation. , Acidization is primarily used to dissolve the minerals contained in coal seams, while the oxidation aims at corroding coal matrix and creating more pores . Acid stimulation has already been applied in the petroleum industry to increase the influence of hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical stimulation is divided into types of acid and oxidation stimulation. , Acidization is primarily used to dissolve the minerals contained in coal seams, while the oxidation aims at corroding coal matrix and creating more pores . Acid stimulation has already been applied in the petroleum industry to increase the influence of hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…The coal seam gas (coalbed methane) emitted in the process of coal mining will not only threaten the safety of mine production and cause casualties but also destroy the ozone layer and cause serious greenhouse emissions. Studies show that methane can cause damage to the ozone layer 7 times as much as carbon dioxide, and the induced greenhouse effect is 20 times as much as that of carbon dioxide at the same quality. In recent years, with the rapid development of the national economy, the depth and intensity of coal mining have been increasing, and the mine gas emission is also increasing rapidly. At the same time, coalbed methane is also a kind of clean energy, and the proven reserves in China are as high as 12 trillion m 3 , which has great potential for development. Coalbed methane development and effective gas extraction can not only reduce gas emissions and gas accidents but also improve the atmospheric environment . Due to the low permeability of most coal seams in our country, the effective extraction range of coal seams is small, the gas concentration is low, the extraction is difficult, and the treatment effect is not ideal. In order to solve this engineering problem, a variety of measures have been taken to increase the permeability of coal seams, such as hydraulic punching, hydraulic fracturing, deep-hole presplitting carbon dioxide phase transformation cracking, etc. In addition, coal surface modification technology has also been widely used in coal seam infiltration. After acid infiltration, this technology changes the pore structure and surface properties of coal, so that the porosity and permeability of the coal seam are increased and the permeability of the coal seam is greatly improved. A multicomponent acid solution treatment of different ranks of coal was carried out by Zepeng et al It was found that the coal sample had a good antireflective effect after acidizing treatment, and the best formula of the acid solution was selected.…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian Journal of Chemical Engineering is acknowledged for dedicating this special issue to the living memory of Dr. Nasr‐El‐Din. This acknowledgment is also extended to the authors who contributed to this special issue [ 1–28 ] as well as the guest editors:…”
mentioning
confidence: 99%